Analisis Beban Kerja, Gaya Kepemimpinan, dan Kompensasi Terhadap Kinerja Karyawan di PT. Ungaran Sari Garment Kabupaten Semarang - Atik Purwati; Sukirman Sukirman (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to analyze the effect of workload, leadership style, and compensation on employee performance at PT Ungaran Sari Garment, Semarang Regency. This quantitative research involved 109 respondents selected using the Slovin formula and purposive sampling. Data were collected using Likert-scale questionnaires and analyzed through multiple linear regression with SPSS 21. The results show that workload and compensation positively and significantly influence employee performance, while leadership style has no significant effect. Simultaneously, all three variables significantly affect performance. These findings indicate that appropriate workload management and a fair compensation system are vital for improving employee performance.